(untitled) (Research, Society and Development, 2021)
Osteosarcoma (OS) is a malignant bone tumor whose treatment is performed through surgical removal associated with combined chemotherapy, which include the use of medications. In order to verify the importance of immunotherapy in a scientific way, researches were carried out in order to confirm the relevance that the study presents as a technological innovation. For this, the PubMed and Science Direct article libraries were accessed to carry out a scientific prospection, a quantity of 278 and 40 with the associations of the descriptors "Bone Neoplasms AND cancer vaccines" and "Osteosarcoma AND cancer vaccines" were obtained, respectively. Regarding technological prospecting, the same descriptors were used and searches were performed in Google Patents, selecting the WO and BR offices when necessary, using the descriptors "bone neoplasms", "osteosarcoma" and "cancer vaccines", presenting a a total of 62,610, 20410 and 34337 patents, respectively for the WO office. In the BR office, 687, 613 and 585 respectively were found. Among these findings, it was possible to notice that the search for immunotherapies for OS is growing, however, the use of vaccines for OS were more present in scientific than in technological prospecting, this can be attributed to the technology of therapeutic vaccines being recent. From these results, it can be concluded that the study provided data from scientific-technological prospection, which can help direct research, highlighting the relevance of prospective technological analysis as an opportunity to invest in intellectual property as a solution to social and economic needs.